Corporate Investment and the Real Exchange Rate - Dao, Mai Chi (IMF Working Papers; Working Paper, 2017)
We examine the relationship between real exchange rate depreciations and indicators of firm performance using data for a sample of more than 30,000 firms from 66 (advanced and emerging market) countries over the 2000-2011 period. We show that depreciations boost profits, investment, and sales of firms that are more financially-constrained and have higher labor shares. These findings are consistent with the view that depreciations boost internal financing opportunities by reducing real wages, thereby spurring investment. We show that these effects on firm performance are enduring, including in the market valuation of firms.